2020
DOI: 10.1101/2020.07.21.068882
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The architecture of the centriole cartwheel-containing region revealed by cryo-electron tomography

Abstract: Centrioles are evolutionarily conserved barrels of microtubule triplets that form the core of the centrosome and the base of the cilium. In the proximal region of the centriole, nine microtubule triplets attach to each other via A-C linkers and encircle a central cartwheel structure, which directs the early events of centriole assembly. While the crucial role of the proximal region in centriole biogenesis has been well documented in many species, its native architecture and evolutionary conservation remain rel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 54 publications
1
31
2
Order By: Relevance
“…1A). This top wheel-like view of a hub decorated with spokes inspired the cartwheel name and is consistent across all species studied thus far, from humans [8] to green algae [1], with the exception of nematodes, where a central tube scaffold was observed instead [3].…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…1A). This top wheel-like view of a hub decorated with spokes inspired the cartwheel name and is consistent across all species studied thus far, from humans [8] to green algae [1], with the exception of nematodes, where a central tube scaffold was observed instead [3].…”
Section: Introductionmentioning
confidence: 53%
“…In most cartwheels studied, pairs of SAS-6 rings were stacked ~5 nm apart, thereby creating an average vertical periodicity at the cartwheel hub of ~4.2 nm [8,21]. It is worth noting that this matches the spacings of cartwheels reconstituted in vitro by Chlamydomonas SAS-6 [21] and suggests that stacking is an inherent property of SAS-6 rings.…”
Section: Cartwheel Stacking and The Emergence Of Centriole Polaritymentioning
confidence: 60%
See 2 more Smart Citations
“…It is well accepted that average cartwheel length is rather conserved within but may differ between distinct cell types and organisms [32]. Whereas recent studies found cartwheel length variation [26,33], it is unclear if this represents changes in the number of stacked rings. Notwithstanding, cartwheels undergo length fluctuations during the cell cycle in Chlamydomonas and Spermatozopsis [34,35] and they disappear during mitosis in human cells (reviewed in [24,25]).…”
Section: Model Predictions and Limitationsmentioning
confidence: 99%